Gender composition in the work environment and physicians’ income from Medicare Part B fee-for-service payments: evidence from longitudinal data - Qing Gong; Xiaochu Hu (Human Resources for Health)
Abstract Background Despite the rising representation of women in the physician workforce, gender-based income disparities persist. In this study, we explore the role of representation of women in the work environment in physicians’ income from Medicare Part B fee-for-service payments and the income gender gap. Methods Our main analytic sample is a balanced panel of 371,472 physicians over 9 years, obtained from the Medicare Part B fee-for-service (FFS) Provider Utilization and Payment Data (2012–2020) from the Centers for Medicare and Medicaid Services (CMS). We use panel regressions with physician and year fixed effects to quantify how total Medicare Part B FFS payments to physicians patient volume, and per-patient payments respond to gender composition changes at the specialty and practice level, controlling for other practice characteristics. We allow the gender composition to have differential impacts on women and men by interacting it with the physician’s gender. In addition, we examined the subsample of physicians who have not switched specialties or practices and explored differences in the effects by practice size. Results Increasing women’s representation in physician work environments impacts men’s and women’s Medicare Part B FFS payments received differently. We find that for women physicians, a 1% increase in the share of women in the same specialty leads to 1.634% higher annual payment, 1.147% more patients, and 0.297% more per-patient payment. Conversely, these effects are reversed for men. Changes in women’s share at the practice level have qualitatively similar effects. Among physicians who have not switched specialties or practices, we still find positive effects for women but no negative effects for men. Furthermore, these effects are stronger in solo or small practices than in large practices. Conclusions Increasing women’s representation in the work environment helps increase the amount of Medicare Part B FFS payments received for women physicians but may reduce payments received for men physicians. Our findings support the efforts in increasing women’s representation in the physician workforce to mitigate gender income disparities and demonstrate the nuanced differences in its impact by gender and the size of the practice to refine policy recommendations.